Circ_0044516 Regulates miR-136/MAT2A Pathway to Facilitate Lung Cancer Development. (25th June 2021) - Chen, Yue-Wei; Du, Qiu-Rong; He, Yu-Juan; Chen, Wen-Shu; Jiang, Wen-Yang; Gui, Qi; Xu, Cheng-Cheng; Wang, Wei; Cheng, Hong-Yun
Abstract : Circular RNA (circRNA) is a type of noncoding RNA that can interact with miRNAs to regulate gene expression. However, little is known concerning circRNA, which is crucial in the pathogenesis of lung cancer. To date, limited studies have explored the role of circ_0044516 in lung cancer progression. Recently, we observed that circ_0044516 expression levels were obviously elevated in lung cancer tissues and cells. A549 and SPCA1 cells were transfected with circ_0044516 siRNA. We observed that knockdown of circ_0044516 dramatically repressed cell proliferation, increased cell apoptosis, and repressed the cell cycle. Moreover, A549 and SPCA1 cell migration and invasion abilities were greatly repressed by circ_0044516 siRNA. Due to accumulating evidence demonstrating the vital role of cancer stem cells, their mechanism of involvement has drawn increasing attention in tumor progression and metastasis research. We also found that cancer stem cell properties were restrained by silencing circ_0044516 in A549 and SPC-A1 cells. Moreover, in vivo xenograft experiments showed that circ_0044516 downregulation reduced tumor growth. Mechanistically, in lung cancer and using bioinformatics, we demonstrated that circ_0044516 sponges miR-136 targeting MAT2A . Furthermore, rescue assays were carried out to identify that circ_0044516 modulates cell proliferation, invasion, and stemness by regulating miR-136 and MAT2A in lung cancer. In summary, our study revealed that the circ_0044516/miR-136/ MAT2A axis is involved in lung cancer progression. Our findings may provide novel targets for diagnosis and therapeutic intervention in lung cancer patients.